Review of existing regional and national programmes of technical and financial assistance to improve regional competitiveness - Williams, Philip (CCS GeorgetownGY, 1993)
Provides a summary of programmes of technical and financial assistance which are already available, to assist regional producers in being more internationally competitive. Looks therefore at regional and sub regional projects such as the CARICOM Export Development Project; the CAIC/IDB/CARICOM Regional Export Development Programme; the Eastern Caribbean States Export Development Agency (ECSEDA); Caribbean Technological Services (CTCS) Network; and Small Enterprise Assistance Project (SEAP). Also examines national programmes in Jamaica, Trinidad and Tobago and Barbados.